O direito de participação democrático no controle concentrado de constitucionalidade das normas: a abertura para discussão de fatos pelo Supremo Tribunal Federal no controle concentrado e a institucionalização do lobby na corte - Carvalho, Rodrigo Barbosa Teles de (2012)
This research intends to identify and analyze the political participation right in the concentrated judicial control. Installed before the Federal Supreme Court (STF) through the possibility/necessity of discussion of facts in these procedures. We start recognizing that the Federal Supreme Court exerts relevant political role in the current Brazilian constitutional order to the point of almost touching the Anglo-Saxon tradition in respect of precedents identified as Common Law, together with a posture of judicial activism of this Constitutional Court in the actual context of political judicialization is curious to note if the democratic paradigm of 1988 Constitution is being fulfilled by STF institutional agency. Constitutional theories which spread open the relation between the Constitution and its (in)effectiveness in social terms with the repercussions of this connection to material constitutional theory will be approached.Considering the constitutional concentrated control of norms in Brazil is usually set apart as abstract, meaning that is not related to a concrete case, it does not possess parts or specific interests, therefore we can argue that there is no need to discuss facts in this model, sufficing an objective analysis of norms - infraconstitutional norm versus constitutional norm - being essential the investigation if it is possible to accomplish this kind of control without fact indagations or if this perusal is inevitable. From a conclusion we try to identify by the democratic constitutional paradigm a political participation right of the citizenry in the concentrated constitutional control procedure, exactly to expand the possibility of the Court knowing the facts brought to procedure by social intervention. With this end we try to evaluate requirement and legitimacy of this acting of society before STF which institutionalize a Lobby in this Court, considering the contra-majority role of constitutional jurisdiction and the influence of this participation in recent STF court trials everything aiming at the search of a better interpretation of constitutional text and the effectiveness of its norms. In this effort trials enacted in STF chambers in which citizenry participation occurred trough process devices as amicus curiae and of public hearings made by concentrated constitutional control of norms was thoroughly scrutinized. The influence of the cited participation and the way by which it was formed considering its role ordinarily attributed was studied to as a result conclude whether this participation engenders an improvement of Brazilian democracy or misguides its fundamental function of constitutional jurisdiction as a defender of the Constitution.